Analisis Konsolidasi dengan Metode Preloading dikombinasikan dengan PVD berdasarkan Perhitungan Analitis dan Plaxis 2d - Baby Purba; Roesyanto Roesyanto; Gina Cyntia Raphita; Rudianto Surbakti (Syntax Corporation Indonesia, 2022)
Soft soil has poor soil characteristics. These soils generally have high compressibility, low permeability and low carrying capacity. Soil improvement by preloading and PVD is one of the common soil improvement methods to speed up the process of soil consolidation. The initial loading is carried out with the aim of consolidating the soft soil layer with the same or more loading amount than the load that will be carried by the soil both during and after construction. While vertical drainage can speed up the consolidation process. This analysis aims to determine the magnitude of consolidation settlement using analytical methods and finite element methods with PLAXIS 2D modeling, the effect of modeling using quadratic triangle elements (6 nodal points) and quartic triangle elements (15 nodal points) on the consolidation magnitude and calculation processing time. The method used in this thesis is the analytical method using Terzaghi's theory and the finite element method using PLAXIS 2D. From the results of the analysis it was found that the use of a quadratic triangle element with 6 nodal points and 15 nodal points did not have a significant effect on the reduction results, but had a large effect on the length of the calculation process. After analyzing using 2D modeling using a quadratic triangle element with 6 nodal points and a quartic triangle element with 15 nodal points, a decrease of -6.673 meters for 6 nodal points and -6.669 meters for 15 nodal points is obtained. There was no significant difference between the two methods, which was only 4 mm different. The time needed to calculate with 6 nodes is about 1 hour and 15 nodes is about 4 hours.